Is Early Preventive Caffeine Safe and Effective in Premature Neonates? A Clinical Trial - Negar Sajjadian; Peymaneh Alizadeh Taheri; Mahboobeh Jabbari (Hindawi Limited, 2022)
Background. Advantages of caffeine for the treatment of apnea of prematurity (AOP) have prompted clinicians to use it as a preventive drug even before the occurrence of apnea. Objective. To compare the effect of early preventive caffeine therapy with routine late preventive caffeine on the occurrence rate of apnea of prematurity, bronchopulmonary dysplasia (BPD) and related radiographic changes, necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH), and patent ductus arteriosus (PDA), the need for mechanical ventilation, the length of mechanical ventilation, and the length of hospitalization. Materials and Methods. In this open randomized clinical trial study, 90 preterm neonates with the gestational age of 25-35 weeks were divided into 2 groups: group A received caffeine during the first two days of life (early preventive caffeine), while group B received caffeine during the third to the tenth day of life (late preventive caffeine). The occurrence rate of AOP and other outcomes were the primary outcomes. The adverse effects of caffeine in each group were the secondary outcomes. Results. The total occurrence rate of AOP was significantly higher (32.6%) in the late group versus (6.8%) in the early group (p=0.002). The total occurrence rate of BPD was also significantly higher (37%) in the late group versus (18.2%) in the early group (p=0.047). On the other hand, we found a lower need for mechanical ventilation, shorter length of mechanical ventilation, shorter length of hospitalization, and a lower occurrence rate of PDA, NEC, and IVH in the early group that was not significant. No adverse effect of caffeine was observed in each group. Conclusions. Early preventive caffeine administration was associated with a significantly lower occurrence rate of AOP, BPD, and BPD radiologic changes. As other outcomes occurred lesser in the early group that were not significant, future studies with more participants are recommended. This study has been registered at the Iranian Registry of Clinical Trials (IRCT20160827029535N8).